FAKTOR PENDUKUNG DAN PENGHAMBAT PERKEMBANGAN AGAMA LOKAL KAHARINGAN PADA ETNIS DAYAK - Dudi, Josef (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
This study aims to determine the driving and inhibiting determinants of the development of local religions Kaharingan on Dayak ethnic in the province of Central Kalimantan-Indonesia. This research employed a qualitative research method with a grounded approach. Based on the research result, it concludes: Firstly, the supporting factor of Kaharingan local religion existence are: 1) existence of reality that Kaharingan trust very strongly influencing social character and social order of civilization of Dayak Ngaju people, 2) Kaharingan local religion becomes the center of a touch of other faith, and 3) the existence of kademangan which is believed to be a social institution as well as a religious institution. Second, at least three factors are inhibiting the development of local religions Kaharingan on Dayak ethnic, namely 1) cultural change, 2) government intervention against customary institutions, and 3) fading mentality "betang".